2,4,6,8-Tetrakis(4-ethylphenyl)-3,7-diazabicyclo[3.3.1]nonan-9-one - Rajesh, K.; Vijayakumar, V.; Safwan, A.P.; Tan, K.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The bicyclo[3.3.1] nonane ring in the title compound, C(39)H(44)N(2)O, adopts a chair-boat conformation with the four benzene rings being directed away from the carbonyl group. The presence of C-H center dot center dot center dot O contacts leads to helical supra-molecular chains along the b axis.